PELATIHAN E-LEARNING UNTUK MENGINTEGRASIKAN TIK DALAM PEMBELAJARAN BAGI GURU-GURU SMA - Ulfia Rahmi; Abna Hidayati; Azrul Azrul (LP2M Universitas Hasanuddin, 2020)
The Training of E-Learning as ICT Integration in Instructional for Senior High School TeachersAbstract. Schools have supporting facilities for implementing e-learning such as computer laboratories, internet networks, wireless access points, and microtia routers. However, the teachers and the school are not ready from the side of human resources. In other words, the school needs training and workshops for teachers to optimize the use of ICT in learning. The purpose of this activity is to train SMA N 4 Kota Pariaman teachers to prepare e-learning to integrate ICT in the learning process. This activity involved all of the 4 SMA N Pariaman teachers in a number of stages, namely a) introduction to the concepts of e-learning and LMS, b) workshops managing LMS, and c) simulations of e-learning applications that had been prepared by each teacher. The results of this training activity are a) the teachers have been able to design learning materials and activities in e-learning and produce learning material packages, b) the teacher readiness in integrating ICT in learning is increasingly increasing, and c) the school readiness to create smart classes with the application of e-learning.Keywords: e-learning, integrate ICT, LMS, teachersAbstrak.Sekolah-sekolah telah memiliki fasilitas pendukung untuk pelaksanaan e-learning seperi laboratorium komputer, jaringan internet, wireless access point, dan microtic router. Namun guru dan pihak sekolah belum siap dari sisi sumberdaya manusia. Sederhananya, pihak sekolah membutuhkan pelatihan dan workshop bagi guru-guru untuk mengoptimalkan penggunaan TIK dalam pembelajaran. Tujuan kegiatan ini adalah melatih guru-guru SMA N 4 Kota Pariaman untuk mempersiapkan e-learning dapat mengintegrasikan TIK dalam proses pembelajaran. Kegiatan ini melibatkan seluruh guru SMA N 4 Kota Pariaman dengan tiga tahap, yaitu a) pengenalan konsep e-learning dan LMS, b) workshop mengelola LMS, dan c) simulasi aplikasi e-learning yang telah disiapkan untuk masing-masing guru. Hasil kegiatan pelatihan ini adalah a) guru telah mampu merancang materi dan aktifitas belajar di e-learning dan menghasilkan paket materi pembelajaran, b) kesiapan guru dalam mengintegrasikan TIK dalam pemebelajaran semangkin meningkat, dan c) kesiapan sekolah untuk menciptakan smart class dengan penerapan e-learning.Kata Kunci: e-learning, integrasi TIK, LMS, guru